Association of intestinal mucosal barrier function with intestinal microbiota in Spleen-Kidney Yang Deficiency IBS-D mice - Liwen Li; Liwen Li; Qi Long; Qi Long; Na Deng; Na Deng; Zhoujin Tan; Zhoujin Tan (Frontiers in Microbiology)
BackgroundTo establish and evaluate an IBS-D mouse model with Spleen-Kidney Yang Deficiency, explore the microecological mechanisms of IBS-D, and provide experimental evidence for the clinical diagnosis and treatment of IBS-D with Spleen-Kidney Yang Deficiency.MethodsSPF-grade female Kunming mice were used to establish an IBS-D model with Spleen-Kidney Yang Deficiency through Folium senna-adenine administration combined with restraint-clamping tail. (1) Clinical symptoms and signs were assessed using diagnostic criteria. (2) The small intestine structure was examined via Alcian blue staining, and intestinal barrier markers like D-LA (D-lactate) and DAO (diamine oxidase) were measured by ELISA to assess pathophysiological changes. (3) 16S rRNA gene sequencing was performed to analyze the intestinal microbiota.Results(I) The model mice exhibited symptoms of IBS-D with Spleen-Kidney Yang Deficiency. (II) ELISA and alcian blue staining revealed elevated levels of D-LA and DAO activity in the model group, indicating damage to the intestinal mucosal barrier structure. (III) Analysis of the intestinal mucosal microbiota in the model group revealed differences in dominant and characteristic bacteria at various taxonomic levels compared with those in the normal group, reflecting an imbalance in the intestinal mucosal microbiota. (IV) Lactobacillus and Lentilactobacillus are associated with mucosal barrier damage in mice modeled by Folium senna-adenine administration combined with restraint-clamping tail.ConclusionThe combination of Folium senna-adenine administration with restraint-clamping tail can be used to successfully establish an IBS-D mouse model with Spleen-Kidney Yang Deficiency. This model leads to damage to the intestinal mucosal structure. Streptococcus, Serratia, Helicobacter, Phocaeicola, and Desulfomicrobium may serve as potential biological markers for the intestinal mucosal microbiota.